Efektifitas Katalog Sebagai Media Promosi Bagi Pengembangan Umkm Di Kabupaten Sragen - Liana Mangifera; Aflit Nuryulia Pramesti; Syahrina Noormala Dewi (Benefit: Jurnal Manajemen dan Bisnis, 2016)
This research aims to identify the promotional mix used bambu craftsmen and formulate an effective promotional strategy for the development of bamboo handicrafts. This research was conducted in the village of Cluster bamboo craft Bendo Sukodono Subdistrict in Sragen. This research used the qualitative approach with key person as a source of information. The data used are the primary data that are taken using the indepth interview. Analysis tool used is content analysis, that perform analysis driskripsi of words that often appear in the indepth interview. This research concluded that the promotion of bamboo craftsmen do is word of mouth and exhibitions. Such promotional efforts is part of this type of direct marketing (direct marketing). The promotion will be optimized if the catalog that contains the task force created the products and pricing that is clear and complete.